Increased antibacterial activity of Cinnamon Oil Microemulsionin Comparison with Cinnamon Oil Bulk and Nanoemulsion - Alireza Valizadeh; Mahdieh Shirzad; Fariba Esmaeili; Amir Amani (Nanomedicine Research Journal, 2018)
Objective(s): Among herbal oils, cinnamon bark oil has several advantages such as anti-inﬂammatory and antimicrobial activity. It is already reported that particle size of oil droplets affects their properties such as their antibacterial activity. In this study, we investigated inhibitory activity of cinnamon oil products including bulk, microemulsion (ME) and nanoemulsion (NE). Methods: ME and NE were prepared by low energy methods. Physicochemical characterization of cinnamon oil ME (COME) and NE (CONE) were investigated. Bulk, ME and NE of cinnamon oil were evaluated for antibacterial inhibitory activity against Escherichia coli and Staphylococcus aureus by microdilution method. Results: Average particle size of COME and CONE was found to be 2040 nm and 30.4 nm, respectively. Results showed that both CONE and COME had increased inhibitory activity (p<0.05) against bacterial infection compared with ablank control group, of which COME had highest antibacterial effects. Conclusions: Our findings suggested COME and CONE as potential green antibacterial agents.